As we saw them the first Japanese Embassy to the United States - Miyoshi, Masao (Kodansha International, 1994)
The story of the first Japanese diplomatic mission to the US. This volume takes a look at cross-cultural relationships and at the roots of intolerance.--Provided by publisher.